PENDIDIKAN ISLAM BERKUALITAS DI ERA MODERN - Yunus, Mahmud (LP3M STAI DARUSSALAM LAMPUNG, 2012)
Education is often measured by changes in external human being, physical and matrial which is to increase the satisfaction of human needs. Therefore, todays educational products trying to make an intelligent and skillful human being, but do not have a soul awareness and a sense of other human beings. This was caused the implementation of education contrary to to the pragmatic measures that have been contaminated by Western ideas of education. In the context of Islam, the function of education will not be achieved when education being offered only human being capable of creating a master of science and technology. Therefore, education should be oriented to the worldly and eternity so that education can create a generation of quality that has IMTAQ and master science and technology.Keywords: Pendidikan Islam, IMTAQ, IPTEK